Desensitization Treatment for Dentin Hypersensitive in Heavy-Smoker Patient - Khofifah, Safitri Dwiwandari; Faizah, Ariyani (Universitas Muhammadiyah Surakarta, 2023)
Introduction: Dentin hypersensitivity (DH) is the most common dental and oral complaint in the world's population, in the form of sharp and short pain as a response to exposure to stimuli on exposed dentin which can occur due to several factors, one of which is gingival recession. Smoking is a factor that causes gingival recession which can cause DH. This case report aims to demonstrate desensitization treatment in a heavy smoking patient with a case of dentin hypersensitivity. Case report: The patient is a 35 year old male with the chief complaint of bad breath and moderate pain in tooth 43, has a bad habit of heavy smoking, up to 20 cigarettes per day. The patient's intraoral examination results had moderate OHI, gingival recession, and positive results on the pain provocation test. The patient experienced gingivitis et causa plaque and calculus accompanied by tooth 43 dentin hypersensitivity. Treatment planning for patients is to provide dental health education (DHE) regarding maintaining oral hygiene and eliminating smoking habits followed by desensitization. Before desensitization, scaling root planing was performed. Desensitization in this case is carried out to treat dentin hypersensitivity with a dual action mechanism desensitization agent (neural action and occlusive action), namely KF 2% topically on the cervical surface of tooth 43 which experienced dentin hypersensitivity due to gingival recession. Results: Dentin hypersensitivity in the patient was successfully treated using a desensitizing agent after repeated topical application of KF 2% four times. Conclusion: Smoking habits can worsen oral health and damage periodontal tissue in the form of gingival recession causing dentin hypersensitivity. DH treatment is desensitization accompanied by DHE to eliminate the cause of dentin hypersensitivity.